2016
DOI: 10.1136/jclinpath-2016-204102
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic lymphoma kinase expression and gene alterations in glioblastoma: correlations with clinical outcome

Abstract: ALK overexpression can be identified in up to 70% of GBMs and does not correlate with underlying gene amplification. Despite being more common in rapidly growing, clinically aggressive GBM, ALK overexpression did not show correlation with prognosis in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 37 publications
4
17
4
Order By: Relevance
“…In the present study, high ALK-1 expression showed a significant association with male sex, however, no significant relation between ALK-1 expression and patient's age. These findings are not matched with the study done by Karagkounis et al [5], which reported that ALK overexpression is more common in older individuals (> 59 years) and that was no association between ALK expression and patient's sex. This discrepancy was due to division of their cases into subgroups according to IDH1 protein expression with cutoff median age of 59 years, which was not implemented in the current study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In the present study, high ALK-1 expression showed a significant association with male sex, however, no significant relation between ALK-1 expression and patient's age. These findings are not matched with the study done by Karagkounis et al [5], which reported that ALK overexpression is more common in older individuals (> 59 years) and that was no association between ALK expression and patient's sex. This discrepancy was due to division of their cases into subgroups according to IDH1 protein expression with cutoff median age of 59 years, which was not implemented in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…ALK-1 positivity was identified as a brown cytoplasmic expression. A four-tier scoring system was used for evaluation of ALK-1 positivity [5]; score 1 was corresponded to weak cytoplasmic expression of ALK-1, moderate cytoplasmic expression was considered as score 2, and strong cytoplasmic expression was considered as score 3 (Fig. 1).…”
Section: Evaluation Of Alk-1 and H-tert Ihc Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a highly hypoxic tumor, which is resistant to conventional chemotherapy or radiotherapy, and of poor prognosis [ 126 ]. ALK overexpression, without ALK gene amplification or translocation, has been shown in human tumors [ 127 ] and in glioblastoma stem cell lines (GSCs) [ 128 ], and ALK signaling has been associated with GSC self-renewal and tumor survival [ 129 ]. Recently, ALK signaling was shown to confer GBMs proliferative advantages through neovascularization [ 130 ].…”
Section: Alk-associated Cancersmentioning
confidence: 99%